Tunning pectinase activity under the effects of electric fields in the enhanced clarification of wine must - Queirós, Mariana; Pereira, Guilherme; Leite, Ana Catarina; Leal, Rita; Rodrigues, Rui; Teixeira, José A.; Pereira, Ricardo N. (Frontiers in Sustainable Food Systems, 2023)
Introduction Pectinolytic enzymes are of great importance for the clarification process of “Vinho Verde” wine must, contributing to the reduction of haze development. During the last decade, a growing body of knowledge has been established about the effects of electric fields on the activation of important food enzymes. However, the influence of electrical parameters on catalytic activity is enzyme-dependent and should be evaluated on a case-by-case basis. This work describes, for the first time, the effects of electric fields and electrical frequency on the activity of pectinase (PEC) in the accelerated clarification of “Vinho Verde” must. Method Moderate electric fields (MEF) with intensities below 20 V/cm and at electrical frequencies ranging from 50 to 20 kHz were applied at temperatures between 15 and 35°C. Enzymatic activity was measured for 25 min, and the initial rate of reaction was determined by the coefficient of the linear plot of galacturonic acid (GAL) production as a function of time. Results The results show that electrical frequency can increase enzymatic activity depending on temperature conditions; at 20°C and with electrical frequencies of 2 and 20 kHz, enzymatic activity increased by up to 40 and 20%, respectively, when compared with the control sample (without the application of MEF). Temperature dependence was evaluated through the Arrhenius equation, showing that energy of activation (Ea) can be reduced from 9.2 to 6.6 kJ/mol at sub-optimal temperatures for PEC activity when MEF is applied. Discussion Electrical parameters, when combined with temperatures below 20°C, reduced pectin concentration in “Vinho Verde” wine must by up to 42% of its initial content. This emergent treatment can be integrated in relevant environmental conditions, presenting an opportunity to increase enzyme efficiency even in low-temperature conditions, which favors the winemaking process.